2008
DOI: 10.2214/ajr.07.2810
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic Detectability of Minute Portal Venous Invasion in Hepatocellular Carcinoma

Abstract: The area of peritumoral hemodynamic change in HCC patients with minute portal invasion (group 1) may be larger than in those without it (group 0), especially when tumors are small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
56
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 19 publications
(17 reference statements)
6
56
1
Order By: Relevance
“…One of the limitations of our study is that we did not compare the relative accuracy between peritumoral hypointensity and other imaging findings that have been described in previous studies (10,33,34,37). Nishie et al (37) and Shirabe et al (33) showed that the areas of peritumoral hemodynamic change or perfusion defects seen on CT during arterioportography (CTAP) or hepatic arteriography (CTHA) were larger in HCCs with minute portal invasion.…”
Section: Discussionmentioning
confidence: 82%
“…One of the limitations of our study is that we did not compare the relative accuracy between peritumoral hypointensity and other imaging findings that have been described in previous studies (10,33,34,37). Nishie et al (37) and Shirabe et al (33) showed that the areas of peritumoral hemodynamic change or perfusion defects seen on CT during arterioportography (CTAP) or hepatic arteriography (CTHA) were larger in HCCs with minute portal invasion.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, several reports have described peritumoral enhancement as a parameter that is suggestive of an increased risk of microvascular tumour invasion [10][11][12]. Kim et al [12] stated that irregular circumferential peritumoral enhancement is a risk factor for microvascular AFP, a-fetoprotein; HBV, hepatitis B virus; HCV, hepatitis C virus; SD, standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Miyata et al [11] reported that distortion of corona enhancement and a tumorous arterioportal shunt on CT hepatic arteriography could be significant predictors of portal vein tumour invasion. Nishie et al [10] reported that the size of the peritumoral enhancement was a significant risk factor for microvascular invasion. In our study, peritumoral enhancement in triphasic CT study was not a statistically significant risk factor for microvascular tumour invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this contradiction may be due to lower contrast resolution of CT and single arterial phase imaging. Nishie et al (23) evaluated the same topic from a different point of view and reported that the area of peritumoral enhancement might be larger in the MVI group, particularly in small HCCs (≤3 cm) with positive and negative predictive values of 71.4% and 75%, respectively (23).…”
Section: Peritumoral Enhancementmentioning
confidence: 99%